Ethno-ornithology : birds, indigenous peoples, culture and society - Tidemann, Sonia; Gosler, Andrew (London ; Washington : Earthscan, 2010)
'An African proverb states that when a knowledgeable old person dies, a whole library disappears. In that light, this book presents knowledge that is new or has not been readily available until now because it has not previously been captured or reported by indigenous people. Indigenous knowledge that embraces ornithology takes in whole social dimensions that are inter-linked with environmental ethos, conservation and management for sustainability. In contrast, western approaches have tended to reduce knowledge to elemental and material references. This book also looks at the significance of indigenous knowledge of birds and their cultural significance, and how these can assist in framing research methods of western scientists working in related areas.'--Publisher's description.
Indigenous knowledges, birds that have'spoken' and science -- Ethno-ornithology and biological conservation -- The broader significance of ethno-ornithology -- The Maori and the Huia -- The impact of red feather currency on the population of the Scarlet Honeyeater on Santa Cruz -- Entrapment Of wetland birds: local customs And methods Of hunting in Krangkeng, Indramayu, Central Java -- Wildlife hunting and bird trade in northern Papua (Irian Jaya), Indonesia -- Transmutation of human knowledge about birds in 16th century Honduras -- Sound, sight, stories and science: avoiding pitfalls in ethno-ornithological research, with examples from Kenya -- What the socals know: comparing traditional and scientific knowledge of Megapodes in Melanesia -- The birds and nature in the stepwells of Gujarat, western India -- Aboriginal stories: the riches and colour of Australian birds -- Tlingit birds: an annotated list with a statistical comparative analysis -- Raven = Heron in Mayan-language prehistory: an ethno-ornithological/linguistic study -- What's in a bird name: relationships among ethno-ornithological terms in Nage and other Malayo-Polynesian languages -- An alternate reality: Maori spiritual guardianship of New Zealand's native birds -- Everyone loves birds: using indigenous knowledge of birds to facilitate conservation in New Guinea -- Birds, people and conservation in Kenya -- Bird messengers for all seasons: landscapes of knowledge among the BriBri of Costa Rica -- The bull of the bog: bittern conservation practice in a Western bio-cultural setting --Towards an Indonesian bird conservation ethos: reflections from a study of bird-keeping in the cites of Java and Bali.
Includes bibliographical references and index
Keywords: Ethnoornithology; Human-animal relationships